Remote assistive technology training in Newfoundland and Labrador's rural schools: Is there a need? | Perceptions des enseignants quant au besoin de formation en technologie d'assistance dans les écoles rurales de Terre-Neuve et du Labrador - Kimberly Maich; Tricia Van Rhijn; Heather Woods; Kimberly Brochu (The Canadian Network for Innovation in Education (CNIE), 2018)
This study examined the perceptions of teachers in rural Newfoundland (NL) about their current ability to support the use of assistive technology (AT) in their classrooms, and identified possible training needs that could be accomplished remotely. Thirty-two educators from rural areas of NL completed an online survey with a mix of closed- and open-ended questions. Five dimensions were explored for this needs assessment including: current beliefs, skills, use, comfort level, and perceptions of AT; identification of specific service needs; learning preferences; available technology; and potential barriers. Results reveal that teachers had positive attitudes about the utility and use of AT in their classrooms, yet were not fully implementing AT with their student's due to a variety of perceived barriers. The study identified a clear need for AT teacher training. Based on the results and the research, literature recommendations are made for teacher training to address the need identified by this study. Cette étude a porté sur les perceptions des enseignants dans les régions rurales de Terre-Neuve de leur capacité actuelle d'appuyer l'usage des technologies d'assistance (TA) dans leurs classes et a cerné de possibles besoins de formation que l'on pourrait combler à distance. Trente-deux éducateurs de régions rurales de Terre-Neuve ont rempli un sondage en ligne comprenant un mélange de questions ouvertes et fermées. Cette évaluation des besoins a exploré cinq dimensions : croyances, compétences, utilisation, perceptions et degré de confort actuels quant aux TA; détermination de besoins de services précis; préférences d'apprentissage; technologie disponible; obstacles potentiels. Les résultats révèlent que les enseignants avaient des attitudes positives quant à l'utilité et à l'utilisation des TA dans leurs classes, mais ne les mettaient pas entièrement en œuvre avec leurs élèves parce qu'ils percevaient une variété d'obstacles. L'étude a cerné un besoin manifeste de formation des enseignants relativement aux TA. Selon les résultats et la recherche, des recommandations sont avancées pour que la formation des enseignants réponde au besoin cerné dans cette étude.